Integrated science teaching materials with local wisdom insights to improve students' critical thinking ability - Yudha Irhasyuarna; Muhammad Kusasi; Fahmi Fahmi; Hery Fajeriadi; Wahyu Redha Aulia; Saidatun Nikmah; Zulfa Rahili (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Critical thinking in science learning emphasizes students' knowledge and understanding of scientific concepts and processes needed to make decisions in real conditions. Students who have the ability to think critically are expected to be able to face problems and make decisions intelligently and based on information to live a better life. This study aims to improve students' critical thinking skills by developing teaching materials based on local wisdom. The results showed that the learning carried out significantly affected the level of critical thinking of students, both viewed as a whole (z=-4.731; p-value=0.000<0.05) or based on three aspects of critical thinking separately (p-value=0.000<0.05). The results of this study recommend that the use of teaching materials with local wisdom in science learning materials, especially materials that make up the ecosystem, must be optimized, both at the school and university levels.Abstrak Berpikir kritis dalam pembelajaran sains menekankan pada pengetahuan dan pemahaman mahasiswa terhadap konsep-konsep ilmiah dan proses yang diperlukan untuk mengambil keputusan dalam kondisi nyata. Mahasiswa yang memiliki kemampuan berpikir kritis diharapkan mampu menghadapi masalah serta mengambil keputusan secara cerdas dan berbasis informasi agar dapat menjalani kehidupan yang lebih baik. Penelitian ini bertujuan untuk meningkatkan keterampilan berpikir kritis mahasiswa dengan mengembangkan bahan ajar berwawasan kearifan lokal. Hasil penelitian menunjukkan bahwa pembelajaran yang dilakukan mempengaruhi tingkat berpikir kritis mahasiswa secara signifikan, baik dilihat secara keseluruhan (z=-4,731; p-value=0,000<0,05), maupun berdasarkan tiga aspek berpikir kritis secara terpisah (p-value=0,000<0,05). Hasil penelitian ini merekomendasikan agar penggunaan bahan ajar berwawasan kearifan lokal dalam materi pembelajaran sains khususnya materi yang membentuk ekosistem perlu dioptimalkan, baik dalam level sekolah maupun pada tingkat perguruan tinggi.